1978
DOI: 10.1073/pnas.75.10.5170
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of beta-endorphin-like immunoreactivity in human ventricular cerebrospinal fluid upon analgesic electrical stimulation.

Abstract: jt-Endorphin-like immunoreactivity in human ventricular cerebrospinal fluid was measured with a specific radioimmunoassay. The subjects were undergoing a surgical procedure for relief of chronic intractable pain. This procedure involved the focal stimulation of a medial thalamic site adjacent to the wall of the third ventricle. Samples were collected before and during the analgesic stimulation. No f-endorphin-like immunoreactivity could be detected prior to stimulation, suggesting that baseline levels are belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(29 citation statements)
references
References 30 publications
1
27
1
Order By: Relevance
“…However, the present results seem to indicate that both high prolactin and low LH concentrations are the results of the same factor, acting through an opioid-mediated mechanism. This is supported by the results of previous experiments in which bromocriptine suppressed prolactin concentrations in lactating sows without influencing LH values (Seren et al, 1984;Mattioli & Seren, 1985 (Akil, Richardson, Barchas & Li, 1978;Akil & Watson, 1980), it might be supposed that a stimulus as potent as suckling would increase the production of opiates. Anatomical bases for such an hypothesis have been shown by Martin & Vogit (1981) and Vanderhaeghen, Lostra, Liston & Rossier (1983) Ellendorff, Elsaesser, Parvizi, Schäkel & Smidt (1985) reported that oxytocin administration in sows after weaning maintains the anoestrus.…”
Section: Resultssupporting
confidence: 77%
“…However, the present results seem to indicate that both high prolactin and low LH concentrations are the results of the same factor, acting through an opioid-mediated mechanism. This is supported by the results of previous experiments in which bromocriptine suppressed prolactin concentrations in lactating sows without influencing LH values (Seren et al, 1984;Mattioli & Seren, 1985 (Akil, Richardson, Barchas & Li, 1978;Akil & Watson, 1980), it might be supposed that a stimulus as potent as suckling would increase the production of opiates. Anatomical bases for such an hypothesis have been shown by Martin & Vogit (1981) and Vanderhaeghen, Lostra, Liston & Rossier (1983) Ellendorff, Elsaesser, Parvizi, Schäkel & Smidt (1985) reported that oxytocin administration in sows after weaning maintains the anoestrus.…”
Section: Resultssupporting
confidence: 77%
“…Direct stimulation of the brain in the areas of these peptide systems, however, causes a rise in CSF ACTH and |)-E and a concomitant physiologic re sponse (analgesia) [1,II,12]. Despite this evidence that CSF ACTH and P-E concentrations may reflect brain activ ity, the value of CSF measurements in neuropsychiatrie ill ness remains speculative [22,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…31, 35]. The precise relationship between brain and CSF concentrations of these hormones is unknown, but there is evidence that CSF concentrations of ACTH, p-E, and other neuropeptides may reflect brain activity [1,6, II,12]. Krieger [22] and others [30] have suggested that assessment of ACTH, p-E, and other neuropeptide concentrations in CSF may provide information to further the understanding of various neuropsychiatric illnesses.…”
mentioning
confidence: 99%
“…In adulthood, a number of biologically active molecules have been proposed to represent CSF signals (Segal, 2000;Brightman and Kaya, 2000). Of special interest are molecules affecting global functions such as sleep and circadian rhythms (Silver et al, 1996;Skinner and Malpaux, 1999), interleukin-1β modulating inflammation and sickness behavior (Krueger and Majde, 1995;Jansson, 1999;Jansson et al, 2000) and β-endorphin being essential for self and species survival (Akil et al, 1978;Bloom et al, 1978;Agnati et al, 1986a;Fuxe et al, 1988a;see Höistad et al, 2005). For a role of CSF signals in diseases of the nervous system, see Fishman (1992).…”
Section: The Cerebrospinal Fluid System As a Communication Channelmentioning
confidence: 99%